THE QUALITY OF HEALTH SERVICES AND THEIR IMPACT ON MEETING PATIENTS’ NEEDS IN SAUDI HOSPITALS - Thamer Saleh Althaibah, Mohsen Theeb S Al Yami, Saleh Hamad H Al Mutyif, Hussain Hamad H Alyami, Abdullah Hamad H Al Mataief, Mohammed Theeb S Alyami, Karimah Atig Hassan Alqadiah, Mohammed Salem M Alyami (Chelonian Research Foundation, 2023)
The current study aims to identify the Quality of Health Services and their impact on meeting patients’ needs in Saudi Hospitals. The study relied on the descriptive analytical approach, while the questionnaire was used as a tool to collect data from the study sample. The study sample consisted of (154) patients at Al-Muzahmiya Hospital in Riyadh. A questionnaire was distributed to them to collect data and then analyze it using SPSS to achieve results. The results of the study showed that there is a high degree of appreciation for the quality of health services in Saudi hospitals, as applied in Al-Muzahmiya Hospital. The results also showed that there is a statistically significant impact at the level of statistical significance (α = 0.05) for the quality of health services (reliability, dependability, tangibility, empathy, responsiveness) in meeting the needs of patients at Al-Muzahmiya Hospital. Based on the results, the study came out with a set of recommendations. Keywords: Quality of Health Services, Patients’ Needs, Saudi Hospitals, Al-Muzahmiya Hospital, Riyadh.